2013
DOI: 10.1080/03079457.2012.760840
|View full text |Cite
|
Sign up to set email alerts
|

Identification of thelic1ABCDoperon that controls the phase-variable expression of phosphorylcholine on lipopolysaccharide fromAvibacterium paragallinarum

Abstract: Phosphorylcholine (ChoP) is an important virulence factor found on the surface of many mucosal pathogens and its expression enhances bacterial colonization on mucous membranes and reduces susceptibility to antimicrobial peptides. Whole-genome sequencing analyses showed that Avibacterium paragallinarum contained an operon with strong sequence similarity to the lic1ABCD operon from Haemophilus influenzae and the pcgDABC operon from Pasteurella multocida; both operons are involved in metabolism and addition of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Another unusual aspect of nematode glycans is the presence of phosphorylcholine; this zwitterionic modification is otherwise known from some bacterial lipopolysaccharides, fungal cell walls and one cestode glycoprotein (Ag5 from Echinococcus granulosus ) (20-22). The phosphorylcholine attached to the N-glycans of one nematode glycoprotein (ES-62 from Acanthocheilonema viteae ) is apparently necessary for the immunomodulatory activity of this protein (23); on the other hand, a possibly contradictory aspect is that phosphorylcholine is recognised by mammalian C-reactive protein (24), a pentraxin whose levels in the serum increases during inflammation.…”
mentioning
confidence: 99%
“…Another unusual aspect of nematode glycans is the presence of phosphorylcholine; this zwitterionic modification is otherwise known from some bacterial lipopolysaccharides, fungal cell walls and one cestode glycoprotein (Ag5 from Echinococcus granulosus ) (20-22). The phosphorylcholine attached to the N-glycans of one nematode glycoprotein (ES-62 from Acanthocheilonema viteae ) is apparently necessary for the immunomodulatory activity of this protein (23); on the other hand, a possibly contradictory aspect is that phosphorylcholine is recognised by mammalian C-reactive protein (24), a pentraxin whose levels in the serum increases during inflammation.…”
mentioning
confidence: 99%
“…2 . Moreover, the LicA, -B, -C, and -D homologs in H. haemolyticus ( 31 ), Histophilus somni ( 32 ), S. pneumoniae ( 16 , 33 ), Streptococcus oralis ( 34 ), Streptococcus mitis ( 35 ), Pasteurella multocida ( 36 ), commensal Neisseria species ( 3 ), Avibacterium paragallinarum ( 37 ), Erysipelothrix rhusiopathiae ( 38 ), and Mycoplasma fermentans ( 39 41 ) have previously been shown to mediate the synthesis of glycoconjugates, such as WTA-, LTA-, and LOS-ChoP structures. In this study, we have identified for the first time the presence of the Lic-1 locus in Proteus mirabilis ( 42 ) and Morganella morganii ( 43 ), both of which express ChoP-modified glycan structures.…”
Section: Resultsmentioning
confidence: 99%